Bio-capped synthesis of TiO2 nanoparticle using Murraya koenigii leaf extract via ultrasonication assisted sol-gel method and its advanced DSSC performance - Yoganand Singh; Himanshu Patel; Ananya Rai; Sakshi Singh; Nikhil Srivastav; Pankaj Srivastava (Next Materials)
In the present study, the synthesis of titanium dioxide (TiO2) nanoparticles (NPs) was investigated and optimized by ultrasonication-assisted sol-gel method using Murraya koenigii (MK) ethanolic extract as a capping agent. In this eco-friendly approach, the MK extract that contained diverse phytochemicals such as flavonoids, carbohydrates, quinones, and alkaloids was utilized as both a reducing and stabilizing agent during nanoparticle formation. The presence of these phytochemicals in MK extract was confirmed using qualitative phytochemical analysis, UV–visible, FTIR spectroscopy and HRMS. Different characterization techniques, including UV–visible measurements, FTIR, XRD, HRTEM and XPS analysis, were employed to analyze the optical properties, crystalline nature, morphology, purity, and size of the synthesized TiO2 nanoparticles. An increased optical band-gap (2.85–3.02 eV) was observed for MK-capped TiO2 compared to bare TiO2 (2.73 eV). The crystallite size and particle size of capped TiO2 nanoparticles were found to be 8.74 nm and 9.2 nm, respectively, which were smaller than the un-capped TiO2. Additionally, specific surface areas and porosity of these nanoparticles were investigated through BET analysis. The results revealed that the capped TiO2 exhibited a higher specific surface area (95.394 m²g⁻¹) compared to the un-capped TiO2 (90.601 m2g−1). Electrochemical impedance spectroscopy (EIS) studies revealed reduced total internal charge transfer resistance in the case of MK-capped TiO2. Notably, the dye-sensitized solar cell (DSSC) fabricated with MK-capped TiO2 exhibited a significantly improved light-to-current conversion efficiency of 3.02 % (Jsc = 10.26 mA/cm2 and Voc = 0.48 V) compared to un-capped TiO2 nanoparticles at 1.76 % (Jsc = 5.92 mA/cm2 and Voc = 0.45 V). The use of MK extract as natural capping agent thus demonstrated its potential to enhance DSSCs output without adverse environmental effects.